Growth and Neutron Diffraction Investigation of Ca3NbGa3Si2O14 and La3Ga5.5Nb0.5O14 Crystals. (14th March 2013) - Kaurova, I. A.; Kuz'micheva, G. M.; Rybakov, V. B.; Cousson, A.; Zaharko, O.; Domoroshchina, E. N.
Abstract : Langanite (La3 Ga5.5 Nb0.5 O14, growth atmosphere: 99% Ar + 1% O2 ) and kanigasite (Ca3 NbGa3 Si2 O14, growth atmosphere: 100% Ar) crystals grown by the Czochralski technique in Ir crucibles along <0001> direction have been firstly investigated by neutron diffraction. The difference between the compositions of upper (La2.935(2) □0.065 )(Ga0.450 Nb0.550(3) )Ga3 (Ga1.965(4) □0.035 )(O13.90(1) □0.10 ) and lower (La2.940(1) □0.060 )(Ga0.590 Nb0.410(2) )Ga5 (O13.82(1) □0.18 ) parts of orange langanite crystal was found. It was established that the colorless Ca3 NbGa3 Si2 O14 crystal grown by using the single-crystal charge has the composition (Ca2.95 □0.05(1) )NbGa3 Si2 O14 and is less defective in comparison to the yellow one grown by using the charge prepared by conventional solid-state reaction. For Ca3 NbGa3 Si2 O14 and La3 Ga5.5 Nb0.5 O14 crystals the possibility of microtwin formation (two unit cells connected by the translation: 1/2 z ) was revealed for the first time. It was found that the difference between the color of crystals is attributed to the qualitative differentiation of oxygen vacancies.